PENGARUH BUDAYA ORGANISASI TERHADAP EFEKTIVITAS MANAJEMEN PENGETAHUAN DI DISPERKIM PEMPROV JABAR (Studi Kasus pada Pegawai Kontrak Harian) - RD. SONNY ABDURRAHMAN (Scientia Regendi, 2021)
Disperkim Pemprov Jabar has not had effective knowledge management yet, accompanied by the existence of issues related to organizational culture. The purpose of this research is to study the influence of organizational culture on the effectiveness of knowledge management. The research method applied is descriptive verificative method with hypothesis test using simple linier regression. The population studied were the daily contract employees in Disperkim Pemprov Jabar, which the sample respondents were taken using Slovin formula and simple random sampling method. The research instrument used is a questionnaire. The research results showed that organizational culture had significant positive influence on the effectiveness of knowledge management. Keywords: Organizational Culture, Knowledge Management Effectiveness.